Molecular clock of viral evolution, and the neutral theory. - Gojobori, T (1990)
Evolution of viral genes is characterized by enormously high speed compared with that of nuclear genes of eukaryotic organisms. In this paper, the evolutionary rates and patterns of base substitutions are examined for retroviral oncogenes, human immunodeficiency viruses (HIV), hepatitis B viruses (HBV), and influenza A viruses. Our results show that the evolutionary process of these viral genes can readily be explained by the neutral theory of molecular evolution. In particular, the neutral theory is supported by our observation that synonymous substitutions always much predominate over nonsynonymous substitutions, even though the substitution rate varies considerably among the viruses. Furthermore, the exact correspondence between the high rates of evolutionary base substitutions and the high rates of production of mutants in RNA viruses fits very nicely to the prediction of the theory. The linear relationship between substitution numbers and time was examined to evaluate the clock-like property of viral evolution. The clock appears to be quite accurate in the influenza A viruses in man.